Emission characterization and performance of conventional liquefied petroleum gas cookstove burners. Issue 1 (1st January 2019) - Fakinle, Bamidele Sunday; Oke, Olawale Daniel; Odunlami, Olayemi Abosede; Sonibare, Jacob Ademola; Akeredolu, Funso Alaba; Oni, Olufemi Sunday
Abstract: The acceptance of liquefied petroleum gas (LPG) cookstove has increased across the country in recent years; however, their performance has not been investigated and established. To achieve this, laboratory tests were carried out to evaluate the thermal efficiency, and industrial combustion analyser (E-instrument E8500) was then used to characterize and quantify the air emissions from combustion of conventional LPG cookstoves in the country. The average thermal efficiency for all tested burners was 66.267 ± 7.218% meeting Tier 4 of the International Organization for Standardization, International Workshop Agreement 11. The mean concentration of CO, NO x, HC, and SO2 was in the range of 3–530, 48–810.5, 99–4176, and 0–4, respectively, and the range of CO2 was 1, 792–3, 592 mg/m 3, which were compared with stationary source limit by Federal Ministry of Environment Standard, Nigeria. The toxicity potential of NO x and SO2 was below unity, 25% of the burners tested were below unity for CO, and HC was higher than unity for all tested burners. Most cookstoves met the guidelines for CO, NO x, and SO2 . Hence, LPG in Nigeria could serve as a source of energy for cooking.